THE INFLUENCE OF ORAL PROBIOTICS ON THE AMOUNT OF ORAL BIOFILM FOUND IN SALIVARY FLUID (Journal of Pharmaceutical Negative Results, 2023)
The purpose of this study was to evaluate the impact that oral probiotics containing the Streptococcus salivarius K12 strain had on the amount of salivary secretory immunoglobulin A, the pace at which saliva was produced, and the amount of oral biofilm. In this double-blind, placebo-controlled, two-arm, parallel-group investigation, thirty-one consenting patients who met the inclusion criteria were recruited. These patients were then randomly allocated into two groups: one receiving probiotics (n = 20) and the other receiving a placebo (n = 20). After 4 weeks of intervention and 2 weeks of washout, the unstimulated salivation rate, concentration of salivary secretory immunoglobulin A, Turesky index, and Papillary-Marginal-Attached index were evaluated. Thirty patients were successful in completing all of the study's requirements. When we compared the probiotic group to the placebo group, we did not find any significant differences in salivary flow rates or levels of salivary secretory immunoglobulin A. The salivary secretory immunoglobulin A concentrations (mg/L) for the probiotic group at baseline and at the end of the study were 230 and 190, respectively, whereas the values for the placebo group were 210 and 180, respectively. At both 4 and 6 weeks, the probiotic group showed a statistically significant reduction in the amount of plaque that had accumulated. Within the confines of the present study, it is possible to draw the conclusion that the consumption of probiotics (Streptococcus salivarius K12) does not influence salivation rates or levels of secretory immunoglobulin A in the saliva, but that it does have a beneficial impact on the accumulation of plaque.